Teams Games Tournament Cooperative Learning on Whole Number Topics to Improve Fifth-Grade Students’ Problem-Solving Skills - Ni Komang Saniska Pratiwi; I Gusti Putu Suharta; Dewi Anzelina (Indonesian Journal of Instruction, 2026)
Mathematical problem-solving ability is an essential competence that must be mastered by elementary school students; however, it remains relatively low due to the dominance of conventional, teacher-centered instruction that limits students’ active participation. This condition necessitates the implementation of innovative learning models that can enhance student engagement and participation. This study aims to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Clash of Champions media on students’ mathematical problem-solving ability. This research employed a quantitative approach using a quasi-experimental design with a posttest-only control group design. The subjects of the study were fifth-grade students selected through a random sampling technique. Data were collected using an essay-type test of mathematical problem-solving ability that had been validated and tested for reliability. Data analysis was conducted through prerequisite tests, including tests of normality and homogeneity, followed by an independent samples t-test to examine the hypothesis. The results revealed a significant difference between students who were taught using the TGT model assisted by media and those who received conventional instruction. It can be concluded that the TGT model assisted by educational game-based media has a significant effect on improving students’ mathematical problem-solving ability. The findings imply that this model can serve as an effective alternative instructional strategy in elementary mathematics learning.